Designing metallic glasses with optimal combinations of glass-forming ability and mechanical properties. (20th March 2021) - Wu, S.J.; Liu, Z.Q.; Qu, R.T.; Zhang, Z.F.
Abstract: It is a long-standing challenge to search for metallic glasses (MGs) with optimal combinations of glass-forming ability (GFA), strength and toughness in the vast compositional space. By taking into account both recently developed ellipse criterion and temperature-based GFA criterion, here we established quantitative correlations among compositions, elastic constants, GFA and mechanical properties of MGs, which enable to predict the GFA, fracture strength and fracture surface simultaneously in advance once the compositions of MGs are determined. Experimental data confirm the validity of this approach in prediction. Finally, a strategy for designing MGs with optimal combinations of strength, toughness and GFA is proposed, which allows for high-throughput discovering glass formers with excellent mechanical properties.